WHY ISLAM IS THE WORLD FASTEST GROWING RELIGIOUS GROUP DESPITE OF TERRORISM ISSUES? AN INITIAL RESEARCH OF TERRORISM ISSUES AND ISLAM AWARENESS - Ucik Ana Fardila; Fardan Mahmudatul Imamah; Intan Sari Dewi (JARES (Journal of Academic Research and Sciences), 2020)
Pew Research Center reported that Islam is the fastest-growing religious group in the world compared to another religious group. The research mentioned that in 2050 Islam population will be 30% of world’s population while Christian will be silghtly more, 31% of world’s population therefore PEW Research Center predicted that in 2100 Islam population will lead religious group’s population even Christian. Terrorism news, extrimist and radical moslem group and Islamophobic culture almost in every western media platforms that rationally contradictory of reality that Islam is the fastest growing religious group. This research is to analyse terrorism issues in mass media and world’s Islam population. Research conducted in qualitative descriptive by literature research methode. The results of the research showed that despite of negative stereotypes in media who tend to correlated Islam and radical moslem group through several platforms such as movie and news, the decision to join Islam was uninfluenced. The stereotypes in news and movies about terrorism, radical moslem group, and extrimist in media could become an initial point for someone to dig information about Islam although it could not concluded as a pure motivation to join Islam.